Advance control of a synchronous reluctance motor drive - Riccio, Jacopo (2023)
This thesis investigates two predictive control algorithms designed to enhance the performance of a synchronous reluctance motor drive. In particular, a finite-control set solution approach has been followed. In particular, this thesis proposes the inclusion of integral terms into the cost function to ensure zero steady-state errors thus compensating for any model inaccuracy. In addition, a control effort term is also considered in the online optimization definition to achieve a quasi-continuous time digital controller given the high achievable ratio between the sampling frequency and the average switching frequency. After a comprehensive simulation study showing the advantages of the proposed approach over the conventional predictive controller solution over a wide range of operating conditions, several experimental test results are reported. The effectiveness of the proposed control approach, including a detailed analysis of the effect of the load and speed variations, is thus fully verified providing useful guidelines for the design of a direct model predictive controller of synchronous reluctance motor drives.